2005
DOI: 10.1089/lrb.2005.3.256
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Vascular Anomalies

Abstract: Hemangiomas and vascular malformations that cause disfigurement or functional limitations may affect the quality life of the affected individual and their families. Negative reaction from strangers, social stigmatization, sadness, stress and low self-esteem are some of the commonly reported effects of having such lesions. Extensive and accurate education about the disease process and advice from support groups may improve quality of life. Psychological intervention may be indicated for some individuals and fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…During the period from 3 years to 7 years, children with visible and significant haemangiomas may have self-image and self-esteem issues 4. Indeed, studies investigating the impact of appearance on behaviour and self-esteem suggest that children with craniofacial anomalies are more introverted and express a more negative self-concept than unaffected children 5 6. Several studies showed that vascular craniofacial anomalies, such as port wine stains, are associated with quality of life (QOL) impairment and lower self-esteem 9 10.…”
Section: Introductionmentioning
confidence: 99%
“…During the period from 3 years to 7 years, children with visible and significant haemangiomas may have self-image and self-esteem issues 4. Indeed, studies investigating the impact of appearance on behaviour and self-esteem suggest that children with craniofacial anomalies are more introverted and express a more negative self-concept than unaffected children 5 6. Several studies showed that vascular craniofacial anomalies, such as port wine stains, are associated with quality of life (QOL) impairment and lower self-esteem 9 10.…”
Section: Introductionmentioning
confidence: 99%
“…To some extent, prior study findings vary with regard to the HRQoL of patients with vascular malformations. For example, some studies have shown that patients with vascular anomalies, or other rare diseases, demonstrated an increased risk of undesirable physical and psychological long‐term consequences, despite treatment outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…Vascular anomalies and related morbidities have been associated with a negative impact on the psychological and social life of patients and families. That is why clinical follow‐ups also need to pay attention to the impact of illness, and its treatment, on psychosocial and quality of life (QoL) outcomes . We need to increase our knowledge of the long‐term outcomes of these conditions and multidisciplinary assessments are needed to address various outcomes, including those that are potentially linked to QoL .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Swelling is common, and local compressive effects can result from extension into adjacent structures such as the orbit, parotid gland, larynx or adjacent musculature. Resulting cosmetic deformity can have profound psychological effects on both patient and parent 9. The cycle of intralesional thrombosis and thrombolysis results in consumption of fibrinogen and production of fibrin split products, with a normal prothrombin time and partial thromboplastin time, termed local intravascular coagulopathy (LIC).…”
Section: Clinicopathologymentioning
confidence: 99%